2021
DOI: 10.1101/2021.12.22.21268219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of the omicron variant virus with the Abbott BinaxNow SARS-CoV-2 Rapid Antigen Assay

Abstract: The US Centers for Disease Control and Prevention recommends rapid testing for SARS-CoV-2 infection as a key element of epidemic control. The Abbott BinaxNow is in widespread use in the United States for self-testing and as part of public health screening campaigns, but has not been evaluated for use with the omicron variant of SARS-CoV-2. We recruited individuals testing positive for COVID-19 PCR at an academic medical center. Anterior nasal swabs were stored in viral transport media and evaluated by viral lo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…Our results reinforce the findings of a smaller study that also examined the analytic sensitivity of the BinaxNOW™ versus Omicron with respect to its ability to detect both variants and in the estimated amount of nucleocapsid protein necessary to visualize a signal 7 . Our findings extend that work by including a larger number of independently collected clinical specimens and widening the range of viral loads in the sample set.…”
Section: Discussionsupporting
confidence: 85%
“…Our results reinforce the findings of a smaller study that also examined the analytic sensitivity of the BinaxNOW™ versus Omicron with respect to its ability to detect both variants and in the estimated amount of nucleocapsid protein necessary to visualize a signal 7 . Our findings extend that work by including a larger number of independently collected clinical specimens and widening the range of viral loads in the sample set.…”
Section: Discussionsupporting
confidence: 85%
“…Our use of live virus, analyte volume, and swab type may explain the slight discrepancy with the manufacturers' LoDs. Our findings are consistent with similar investigations, but these studies fell short of the FDA's EUA requirement of 20 LoD replicates or included tests unavailable in the United States (15)(16)(17). In all, we demonstrate that the rapid antigen tests evaluated detect Omicron effectively, allaying concerns on the impact of the nucleocapsid mutations.…”
Section: Introductionsupporting
confidence: 91%
“…Using an FDA Emergency Use Authorized antigen test, a recent study showed detection of Omicron and Delta specimens with concentrations of 100,000 copies per swab or greater. 18 In this study, we determined the analytical sensitivity of a rapid antigen test with SARS-CoV-2 variants, including Omicron, Delta, Alpha, and Gamma. Our data show that the rapid antigen test has the lowest limit of detection with Alpha and Gamma (10 PFU/mL), followed by Omicron (100 PFU/mL) and Delta (1,000 PFU/mL) (Fig.…”
Section: Discussionmentioning
confidence: 99%